The Importance of Linkers in the Structure of PSMA Ligands - Uspenskaya, Anastasia A; Nimenko, Ekaterina A; Machulkin, Aleksei E; Beloglazkina, Elena K; Majouga, Alexander G (Current medicinal chemistry, 2022)
Cancer is one of the leading social problems of the modern world. Today prostate cancer is the second leading cause of cancer deaths among men. Targeted drug delivery is widely used to treat and diagnose prostate cancer. Conjugates selectively binding to prostatespecific membrane antigen-based on urea ligands are being actively developed against this disease. The linker has a significant influence on the biological activity of such conjugates. The linker performs a large number of functions, and its modification is one of the key methods for creating the best pharmacological profile. This review aims to discuss and analyze the main approaches to the method of introduction and synthesis of linkers for this type of conjugates without a description of the influence of biologically active molecules, as well as to establish the key modification methods that have a significant role on the structure-activity relationship. For this purpose, a review of the current scientific literature was performed, both for the conjugates under development and those already undergoing clinical trials. It was found that the optimal structure is a linker containing an aliphatic fragment near the vector- molecule (n(CH2) = 3-6), followed by a polypeptide chain consisting of 2 to 4 amino acid residues. The presence of a Phe-Phe dipeptide chain or the introduction of negatively charged groups also has a positive effect. Ongoing research in this field helps to establish the accurate effect of each linker fragment, and the development of solid-phase synthesis methods makes it much easier to achieve this goal.